Minimum Wage in Colombia and the Oil Palm Sector - Federación Nacional de Cultivadores de Palma de Aceite, Fedepalma (Federación Nacional de Cultivadores de Palma de Aceite, 2021)
Our commitment toward achieving the sustainability of the palm oil industry in Co¬lombia has led us to work on various scenarios in order to provide tools that allow this sector to make improved decisions, adopt good practices, prevent risks, and contribute to meet the sustainable Development Goals.
Keywords: Agroindustria; Salario mínimo; Mercado laboral; Producción; Colombia; Hogares; Economía; Empleo